Typification of names in Kaunia (Asteraceae, Eupatorieae, Oxylobinae) - Viera Barreto, Jessica Noelia; Gisela, Sancho (Phytotaxa, 2014)
During the revision of Kaunia (in prep.), we detected names which required typification or whose current typification was incorrect. After the analysis of protologues and original material, we designated six lectotypes and one neotype for seven names currently assigned to Kaunia, and we superseded one lectotype. We discuss the details for each case.